Assessing urban vitality and its determinants in high-speed rail station areas in the Yangtze River Delta, China - Lei Wang; Wei Zheng; Sanwei He; Sheng Wei (Journal of Transport and Land Use, 2022)
Unlike most city centers in countries that pioneer European high-speed rail (HSR) lines, HSR stations in China have mainly been developed in suburban areas. The rationale for peripherally located HSR stations is due to development costs and intentions to speed up urbanization and develop new suburbs. However, it remains unknown whether the HSR-led urban development policy is effective as intended, despite the rise of HSR area suburbs. Taking the Yangtze River Delta (YRD) as an example, this study assesses HSR station area urban vitality (SAUV). It constructs an indicator system comprised of concentration, accessibility, liveability, and diversity of physical facilities and socioeconomic activities. It compares the rank-size distribution of urban vitality in different station types: conventional rail (CR), upgraded-HSR, and newly built HSR stations. The spatial differentiation and influence factors of SAUV in the YRD are further examined among cities and provinces of different station types and HSR lines. The results show that station areas with high urban vitality are mainly distributed along major economic corridors. Only a few newly built HSR stations could attract vibrant urban activities. More vibrant economic activities could be clustered in HSR station areas in provincial-level cities and along the Shanghai-Nanjing HSR line. Although the SAUV value is strongly associated with local socioeconomic contexts, it is significantly influenced by the administrative rank of cities, station-city transit connectivity, and frequency of train services. This study suggests that integrating multilevel spatial planning with vitality-led urban development is necessary for the sustainability of the HSR economy.